Analysis of maximum flood records in the arid environment of Saudi Arabia. Issue 1 (1st January 2020) - Ewea, Hatem A.; Al-Amri, Nassir S.; Elfeki, Amro M.
Abstract: A collection of rainfall data and flood records for ephemeral channels in the Kingdom of Saudi Arabia (KSA) provided a unique opportunity to analyze the extreme records in such arid environment. Data of 3121 records were collected. A regional flood envelope relationships and other envelope curves in similar arid areas were compared with the current study. We found that the envelope of the maximum-recorded peak discharge versus basin area follows Q p max = 700 A 0.26 . The exponent falls in the range of the exponents in other arid basins. The enveloping curve for the volume versus basin area is V max = 0.0004 A 1.7 . The parameters of the equation are significantly different from that of the arid Negev desert, Israel. Derived peak flow–volume relationship has the form V max = 400 × 10 3 Q p 1.2 . We found such relation is similar to arid/semi-arid southwestern United States but with slightly higher exponent and constant. When the peak discharge and maximum volume are plotted against their accompanied rainfall depth, p, linear envelope in log- log plot are developed for KSA region: Q p max = 76 p 0.8 and V max = 680 × 10 3 p 0.77 . The equations predict the upper limit of the expected peak discharges and volumes that can be used for hydro-engineering applications in ungauged basins in the study region and regions a like. The developed envelope curves can also be used as an alternative or guide to performing rainfall-runoff modeling in KSA. The volume-area envelope equations have high degree of credibility since, 92% of the published data used for validation falls within the upper and lower envelope limits. These envelope curves have to be updated when more records are available.